Problems of Early Diagnosis of the Abdominal Cavity with Concomitant Abdominal Trauma in Children (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: polytrauma; concomitant trauma; catatrauma; complex diagnostics; abdominal trauma